History of current non-insulin medications for diabetes mellitus - Celeste C. L. Quianzon; Issam E. Cheikh (Greater Baltimore Medical Center, 2012)
This article is a brief review of the current non-insulin agents for diabetes mellitus in the United States, namely, sulfonylureas, biguanides, thiazolidinediones, meglitinides, α-glucosidase inhibitors, glucacon-like peptide-1 receptor agonists, dipeptidyl-peptidase-4 inhibitors, amylin agonists, bromocriptine, and colesevelam.